2021
DOI: 10.1001/jamanetworkopen.2021.40458
|View full text |Cite
|
Sign up to set email alerts
|

Association of Neuraxial Labor Analgesia for Vaginal Childbirth With Risk of Autism Spectrum Disorder

Abstract: IMPORTANCERecent studies have reported conflicting findings regarding a potential association between analgesia used during labor and autism spectrum disorder in the offspring. OBJECTIVE To evaluate whether neuraxial labor analgesia increases the risk of autism spectrum disorder in the offspring. DESIGN, SETTING, AND PARTICIPANTS This cohort study included mother-child dyads who underwent vaginal delivery and were exposed to neuraxial labor analgesia. Delivery data were collected from the Medicaid Analytic eXt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…The last two studies by Hanley et al and the most recently published by Straub et al demonstrated a small increase in the risk of ASD in the offspring exposed to ELA [ 15 , 18 ]. The first study included 388,254 term singleton vaginal deliveries in British Columbia, Canada between 1 April 2000, and 31 December 2014, with the follow-up up to 31 December 2016.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The last two studies by Hanley et al and the most recently published by Straub et al demonstrated a small increase in the risk of ASD in the offspring exposed to ELA [ 15 , 18 ]. The first study included 388,254 term singleton vaginal deliveries in British Columbia, Canada between 1 April 2000, and 31 December 2014, with the follow-up up to 31 December 2016.…”
Section: Resultsmentioning
confidence: 99%
“…The research by Qiu et al which reported 37% increase in the risk of ASD development in the offspring exposed to ELA is so far the only study to prove significant association. The later published five cohort studies reported HRs between 1.05 and 1.11 with pooled adjusted HR of 1.07 reflecting a lack of significant interrelation [ 18 ]. The study by Qiu et al was widely criticized and many limitations were identified by the experts.…”
Section: Discussionmentioning
confidence: 99%
“…15 In addition, a nationwide cohort study of public and private US insurance records reported a small risk increase (aHR, 1.08; 95% CI, 1.02-1.15). 18 Its authors also reported the pooled effect estimate from a metaanalysis they conducted of published cohort studies (aHR, 1.10; 95% CI, 1.06-1.13). 18 Despite the use of similar case-finding algorithms, covariates, and post hoc analyses, the differences in findings across the Canadian and Danish studies highlight the challenges of comparing the results from disparate administrative data sources.…”
Section: Discussionmentioning
confidence: 99%
“…18 Its authors also reported the pooled effect estimate from a metaanalysis they conducted of published cohort studies (aHR, 1.10; 95% CI, 1.06-1.13). 18 Despite the use of similar case-finding algorithms, covariates, and post hoc analyses, the differences in findings across the Canadian and Danish studies highlight the challenges of comparing the results from disparate administrative data sources. Regional variations in how ASD diagnoses are captured and the quality and quantity of exposure and covariate data are all likely to change the magnitude and direction of reported associations.…”
Section: Discussionmentioning
confidence: 99%
“…Straub et al 18 published a study with over 1.6 million subjects, the largest sample size compared with the beforementioned studies. This study used a propensity matching score to control for confounders; it also showed no association between increased risk of ASD and the use of epidural labor analgesia.…”
Section: Prenatal Origins Of Autism Spectrum Disordermentioning
confidence: 99%